Improving antibiotic prescribing for children in the resource‐poor setting. (March 2015) - Le Doare, Kirsty; Barker, Charlotte I. S.; Irwin, Adam; Sharland, Mike; Waller, Derek
<x xml:space="preserve">Abstract</x> Antibiotics are a critically important part of paediatric medical care in low‐ and middle‐income countries (LMICs), where infectious diseases are the leading cause of child mortality. The World Health Organization estimates that >50% of all medicines are prescribed, dispensed or sold inappropriately and that half of all patients do not take their medicines correctly. Given the rising prevalence of antimicrobial resistance globally, inappropriate antibiotic use is of international concern, and countries struggle to implement basic policies promoting rational antibiotic use. Many barriers to rational paediatric prescribing in LMICs persist. The World Health Organization initiatives, such as 'Make medicines child size', the Model List of Essential Medicines for Children and the Model Formulary for Children, have been significant steps forward. Continued strategies to improve access to appropriate drugs and formulations, in conjunction with improved evidence‐based clinical guidelines and dosing recommendations, are essential to the success of such initiatives on both a national and an international level. This paper provides an overview of these issues and considers future developments that may improve LMIC antibiotic prescribing.